Analisa Technology Acceptance Model Untuk Implementasi Single Sistem Operasi Di Terminal Petikemas Makassar - Rangga Aksara, Frenda; Usman, Osly; Agung Priambodo, Ervin (Fakultas Ekonomi Universitas Gresik, 2023)
This study aims to measure the level of acceptance of the use of the system using the TAM (Technology Acceptance Model) theoretical analysis on the implementation of a single operating system at the Makassar Container Terminal. A single operating system consisting of a terminal operating system and a customer portal is something new for users at the Makassar Container Terminal, so it is necessary to measure the level of acceptance of this application to get feedback from users with the factors of the technology acceptance model. The research methodology uses a quantitative research method using a questionnaire as a data collection instrument. After tabulating the data, then the data is tested statistically descriptive, then analyzed by testing the measurement model (inner model) and testing the structural model (outer model). The results of testing the hypothesis produce that the Perceived Ease Of Use instrument has a positive and significant effect on Perceived Usefulness in the use of a Single Operating System, then the Perceived Ease Of Use instrument has a positive and significant effect on Attitude Toward Using in the use of a Single Operating System. Then the relationship between Perceived Usefulness with Attitude Toward Using and Behavioral Intention also has a significant and positive impact on this study, then Attitude Toward Using produces a significant and positive influence on Behavioral Intention, and in the last hypothesis it is also proven that Behavioral Intention has a positive and significant influence on Actual Usage using a single operating system application at the Makassar Container Terminal